Insecticidal and repellent property of selected zingiberaceae species against medically important mosquitoes / Restu Wijaya Mahardika - Restu Wijaya , Mahardika (2017)
Mosquitoes are the vectors for transmitting severe and well-known illnesses such as malaria, yellow fever, dengue fever, chikungunya, filariasis, encephalitis, West Nile virus and Zika virus. These diseases produce significant morbidity and mortality in human worldwide. Of late the utilisation of environment friendly and biodegradable natural insecticides of plant origin are preferred because synthetic insecticides not only cause development of resistance in vector species but are also harmful to man and environment. Hence, this study explored the effects of hexane and dichloromethane extracts of Zingiber officinale var. rubrum (HZOR and DZOR), Zingiber montanum (HZM and DZM), Zingiber spectabile (HZS and DZS), Zingiber zerumbet (HZZ and DZZ) and Curcuma aeruginosa (HCA and DCA) on larvicidal, adulticidal and repellent activities against Aedes albopictus, Aedes aegypti and Culex quinquefasciatus. The hexane and dichloromethane extracts were prepared by soaking the rhizome powder into two organic solvents, hexane and dichloromethane separately and then were filtered and evaporated. The yield obtained from hexane and dichloromethane extracts of Z. officinale var. rubrum, Z. montanum, Z. spectabile, Z. zerumbet and C. aeruginosa were 3.29%, 6.97%, 3.09%, 9.44% and 9.09%, respectively. The larvicidal and adult mortality were observed after 24 h of exposure; no mortality was observed in the control group. Results of log-probit analysis (at 95% confidence level) revealed that HZS, HZOR and HZM were noted to be active against the larvae of Ae. albopictus (LC50= 93.51, 96.86, 99.04 mg/L; LC90= 168.65, 168.65, 153.77 mg/L, respectively). The HZZ and HZM were recorded to be active against larvae of Ae. aegypti (LC50= 82.05, 84.95 mg/L; LC90= 121.05, 134.85 mg/L, respectively) whereas, HZZ, DZZ, HCA and DCA were noted to be highly active against larvae of Cx. quinquefasciatus (LC50= 49.28, 30.15, 21.94, 42.47mg/L; LC90= 83.87, 82.62, 66.61, 99.05 mg/L, respectively). The highest adult mortality was only observed against Ae. albopictus mosquito and was found in HCA, HZS, HZZ and DZS with 37.78%, 24.44% 20.00% and 15.56%, respectively. Of the five Zingiberaceae species tested for repellent activity against the three mosquitoes at 1,000 mg/m2, HZM and DZM were the most effective with 89.33% and 85.33% repellency against Ae. aegypti mosquito. Therefore, these results suggest that hexane and dichloromethane extracts of Z. officinale var. rubrum, Z. montanum, Z. spectabile, Z. zerumbet and C. aeruginosa have the potential to be developed as bio-insecticides to control the larvae, adult and as repellent agents for Ae. albopictus, Ae. aegypti, and Cx. quinquefasciatus.